Multi nutrient functional biscuits “Tumiz” improve nutritional status and growth of children; A clinical trial in malnourished rats. - Nadimin, Nadimin; Asikin, Hijrah; NYIN, Ang Yeow; THIEN, Lee Shoo; ABIDIN, Azrina Zainal (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: The main cause of malnutrition in Indonesia is insufficient nutrient intake, necessitating efforts to supplement nutrients through supplementary feeding. Conversely, Indonesia possesses a variety of local food ingredients that remain underutilized, thus requiring processing to enrich the nutrient content of snacks for combating malnutrition.malnourished Wistar rats. Methods: Employing a randomized control group pretest-posttest design, male Wistar rats divided into four groups, each comprising 6 samples. These groups included K1: normal rats fed standard food, K-2: malnourished rats given biscuits from the Ministry of Health program, K-3: malnourished rats fed normal food, and K-4: malnourished rats given Tumiz biscuits. The intervention spanned eight weeks, during which body weight, body length, albumin, IGF-1, and MDA levels were measured before and after the intervention. Results: Significant increases in body weight were observed between pretest-posttest in all groups. The greatest increase in body weight over two months was found in group K4. The albumin levels increased in the rats, there was no statistically significant difference in albumin levels before and after the intervention acrossall groups: K1 (p=0.336), K2 (p=0.297), K3 (p=0.191), and K4 (p=0.466). All intervention groups experienced a significant increase in body length (p<0.05), including groups K1 (p<0.001), K2 (p=0.003), K3 (p<0.001), and K4 (p<0.001). The increase in body length of group K4 did not differ from group K1. IGF-1 levels of Wistar rats significantly increased in group K4 (p=0.006) and group K2 (p=0.026), while groups K1 and K3 experienced a decrease in IGF-1 levels. There was no difference in MDA levels before and after the intervention across all groups. Conclusion: Tumiz biscuits can increase body weight, body length, and IGF-1 levels but have not been able to increase albumin levels in malnourished Wistar rats. Tumiz biscuits did not reduce MDA levels in malnourished Wistar rats.